Analysis of Green Marketing Mix and the Purchase Intention of Environmentally Friendly Product - Alivia Zahra Kirana Dewi; Yuli Liestyana; Tri Wahyuningsih; Yekti Utami; Hadi Oetomo; Tugiyo Tugiyo; Sudaryatie Sudaryatie (AIBPM Publisher, 2024)
The study aims to analyze the effect of green marketing on the purchase intention of environmentally friendly products. The variables used are green product, green price, green place, green promotion, and purchase intention. This research uses quantitative methods. The data collection method was a questionnaire distributed to 132 respondents who knew about environmentally friendly products. The analytical method used is multiple regression analysis. The results of this research show that green products, green prices, and green promotions have a positive effect on purchase intention. Meanwhile, green places do not positively influence purchase intention. Green places do not affect purchase intention because the location or distribution of environmentally friendly products is not a consideration for potential buyers. Several factors may have caused the green place not positively to affect purchase intention. However, researchers have not examined this; it is hoped that future researchers can examine the phenomenon of green places not positively affecting purchase intention.